Bacteriorhodopsin's L550 intermediate contains a C14-C15 s-trans-retinal chromophore. - Fodor, S P (1988)
Conformational changes of the retinal chromophore about the C14-C15 bond in bacteriorhodopsin (BR) have been proposed in models for the mechanism of light-driven proton transport. To determine the C14-C15 conformation in BR's L550 intermediate, we have examined the resonance Raman spectra of BR derivatives regenerated with retinal deuterated at the 14 and 15 positions. Vibrational calculations show that the C14-2H and C15-2H rocking modes form symmetric (A) and antisymmetric (B) combinations in [14,15-2H]retinal chromophores. When there is a trans conformation about the single bond between C14 and C15 (14-s-trans), a small frequency separation or splitting is observed between the A and B modes, which are found at approximately equal to 970 cm-1. In 14-s-cis molecules, the splitting is large, and the Raman-active symmetric A mode is predicted at approximately equal to 850 cm-1. In addition, the monodeuterium rock should appear at an unusually low frequency (920-930 cm-1) in the 14-2H-labeled 14-s-cis molecules. These patterns are insensitive to computational details: similar results are predicted by a modified Urey-Bradley force field and by MNDO (modified neglect of differential overlap) calculations for twisted chromophores and for highly delocalized protonated Schiff base cations. Time-resolved resonance Raman spectra were obtained of BR's L550 intermediate regenerated with [14-2H]-, [15-2H]- and [14,15-2H]retinal. The symmetric A rock in L550 is found at 968 cm-1, within 4 cm-1 of the frequencies for the monodeuterio derivatives, and no scattering is observed between 800 and 940 cm-1. The rocking frequencies of deuterated L550 are within 5 cm-1 of those observed in BR568, which contains a 14-s-trans chromophore. These results show that L550 contains a 14-s-trans chromophore and suggest that only 14-s-trans structures are involved in the proton pumping photocycle of BR.